Hepatic portal venous gas: A case report and review of literature - Kesarwani, Vikas (Medknow Publications, 2009)
Hepatic portal venous gas (HPVG) results from mesenteric ischemia and a wide variety of other causes. The primary factors that favour the development of this pathologic entity are intestinal wall alterations, bowel distension, and sepsis. Findings of HPVG during an ultrasound or computed tomography (CT) scan should be carefully evaluated in the context of the clinical picture. In the absence of features of bowel ischemia, the prognosis of patients with HPVG is usually good.